PERLINDUNGAN HAK ANAK DALAM KANDUNGAN TERHADAP TINDAKAN ABORSI DALAM SEBUAH PERKAWINAN DI INDONESIA (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2022)
This act of abortion continues to happen in the community even though abortion is illegal fvwbd. Abortion is the act of ending a pregnancy by removing the consequences of conception before the fetus can live outside the uterus. The aim of this studybdvjewvjhq is to focus on imparting understanding and knowledge regarding the protection of children's rights against abortion under positive law in Indonesia. Use normative research methods by studying law and design, and using primary, secondary, and tertiary law sources. Marriage includes the basic needs of every human being for the purpose of forming a happy family or household, and marriage for the purpose of having children, and children are a command given by almighty God. , even children are called the most valuable inheritance of wealth. There is Law No. 35 of 2014gwgfx explaining the changes in Law No. 23 of 2002 relating to the protection of children, which stipulates that a child is a person who has not reached the age of 18 (eighteen) years, including children under the age of 18 (eighteen years). in utero age. In the Health Act No. 36 of 2009, the provisions regarding abortions based on signs of a medical emergency were abolished and pregnancy was a form of sexual harassment. However, in the Penal Code that regulates abortion, it is very clear that it is objectionable for any reason and under any conditions because abortion is murder leading to death. But in Islamic law there are Ustashi who say they allow abortion but there are also those who do not. Therefore, it should be known that this abortion has been regulated by Indonesian yang law and Islamic law, but in this regulation there are problems with the rules that form the application of the rules that are not in accordance with the procedure. of these crimes.